Safety and efficacy of elbasvir/grazoprevir in patients infected with hepatitis C virus genotype 4 in Qassim region of Saudi Arabia - Murgod, Shivananda E.; Ahmed, Sumaira; Almutairi, Nawaf; Alqifari, Abdullah; Alharbi, Majed; Shoqueer, Ahmed (International Journal of Health Sciences, 2023)
Objective: Untreated hepatitis C virus (HCV) infection can lead to cirrhosis, hepatocellular cancer, and even death and also increases liver diseases. The elbasvir/grazoprevir (EBR-GZR) treatment regimen when given in HCV genotype (GT) 1 and GT4 infection for 8 or 12 weeks showed a high sustained virolgical response (SVR) rates in different populations. This study was assessed the effectiveness as well as safety of EBR-GZR in 12 week treatment regimen in HCV GT4-infected treatment naïve Saudi patients. Methods: This study conducted from June 2017 and December 2020 on Saudi HCV patients infected with GT4. Treatment protocol was given for 12 weeks in treatment naive HCV GT4 infected cirrhotic and non-cirrhotic participants which were later followed for a total of 24 weeks for safety and efficacy of EBR-GZR. Results: We analyzed data of 54 participants with HCV GT 4 infection. Mean age was (53.46 ± 14.94) Treatment regimen was given to 14 cirrhotic (F4) and 40 noncirrhotic (F0–F3). SVR was seen in 98.1% of participants with tolerable side effects and improved model for end stage liver disease (MELD) scores as fall in percentage seen from 18.5% to 14.8% in participants with MELD > 10. Conclusion: This retrospective study confirms that EBR-GZR for 12 weeks is a safe and effective treatment regimen in HCV GT4 patients in studied Saudi population. Treatment completion was followed by high SVR12 rates with improvement in prognostic markers of liver disease in participants with compensated cirrhosis. In short, the EBR-GZR combination showed efficacy in achieving the SVR12 in Child-Pugh B cirrhotic and non-cirrhotic population with a favorable safety profile.